Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/2167479515595500
|View full text |Cite
|
Sign up to set email alerts
|

Does the Game Really Change? How Students Consume Mediated Sports in the Age of Social Media

Abstract: Social media have been said to rival traditional media in the realm of sports. Actual evidence for a change in consumption patterns, though, remains scarce. This study investigates college students’ use of multiple distribution systems in the context of sports. More specifically, the relative importance of Twitter in relation to television is assessed. In addition, variables potentially predicting a greater reliance on Twitter are analyzed. Results indicate that television remains the primary distribution syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…As previous studies found that a decent share of tweets included some kind of expression of sympathy for one team, using such information could be a promising approach [ 29 ]. However, people turn frequently to Twitter to discuss on-going events during live sporting contests, especially if they perceive themselves as experts [ 30 ], irrespective of their rooting interests. Consequently, only using tweets of the involved fanbases can lead to a significant decrease of tweets that can be used for further analyses.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies found that a decent share of tweets included some kind of expression of sympathy for one team, using such information could be a promising approach [ 29 ]. However, people turn frequently to Twitter to discuss on-going events during live sporting contests, especially if they perceive themselves as experts [ 30 ], irrespective of their rooting interests. Consequently, only using tweets of the involved fanbases can lead to a significant decrease of tweets that can be used for further analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Kassing and Sanderson (2015) illustrated the ways in which social media channels can move beyond parasocial interaction into more typical social exchanges (i.e., circumsocial interaction). However, Boehmer (2016) indicated that a large majority of fan/athlete interaction in social media channels remains parasocial, or one-way in nature with athletes or sports figures frequently not responding to individual social media messages. In the case of Snapchat, little to no evidence was found in both the narrative collection and motive scale development phases of this study to indicate that sports fans are specifically motivated by two-way communication with athletes or sports figures when using Snapchat to follow sports.…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous fast development of communication technology, social media have already become the main venue where people encounter news today (Mitchell, Holcomb, & Page, 2013). For sports communication, the organizations of media, athletes, and sports teams were more likely to share sources and attain more substantial attention through social media (Boehmer, 2016). On such social-focused applications as Twitter, Facebook, Instagram, and Snapchat, sports have become one of the most viewed topics already (Mitchell, Kiley, Gottfried, & Guskin, 2013).…”
Section: Sports and Social Mediamentioning
confidence: 99%
“…This is mainly due to the fact that Twitter itself has been pushing for the platform to be utilized in sports domain (Rogers, 2014). Also, instant communication with strangers is allowed on Twitter, while only people who followed each other can contact on Facebook (Boehmer, 2016).…”
Section: Sports and Social Mediamentioning
confidence: 99%